THE ENVIRONMENTAL MANAGEMENT OF THE SEGARA ANAKAN LAGOON AND ITS SURROUNDINGS, CILACAP, CENTRAL JAVA – INDONESIA - Joko Christanto (Universitas Negeri Yogyakarta, 2009)
This paper is heavily drafted from a research conducted at Segara Anakan Lagoon in 2000. The lagoon is located on the south of Central Java coast and immediately to the northwest of Cilacap District, Central Java Province, and it is about 350 km southeast of Jakarta. The lagoon and its surroundings are marked by several distinctive features, including an extensive mangrove system, very rapid sedimentation, leading to progradation of the shoreline, strong tidal influence and the presence of many fish, crab and shrimp varieties. The main objective of the paper is to prepare the Segara Anakan environs so as to ensure that economically and socially valuable ecosystems are protected for the benefit of current and future generations. The method applied in the study was descriptive analysis of the collected secondary data to support the results of the study. The results of the study showed that commercial cutting and degradation of the mangroves must be controlled through related and concerned agencies, and there was a need to prepare more sustainable basis for conserving and developing the lagoon’s resources in the future. On the basis of the study results, formulated recommendation is as the following: the mangrove forest need to be protected by preparing forest management guidance and instructions that can easily be accessed and operated by Kampung Laut people. Besides, the Kampung Laut people should have defined areas to be used for various purposes such as agricultural activities, ponds and regeneration areas. The mangrove forest in the surrounding Segara Anakan lagoon must be a protected zone, and the best option is likely by applying a community-based management. This emphasized local, village level, and control of resources utilization. Key words: environment, degradation, lagoon, management, mangrove forest, Segara Anakan, Cilacap District and Central Java Province.